Densidade inicial de plantio e seus efeitos na produção de biomassa e carbono, no crescimento e no sortimento de madeira de Pinus taeda L. - Vale, Aline Beatriz do (2020)
The objective of this research was to evaluate the influence of the initial planting density on the production of biomass and carbon, on the growth of dendrometric variables and on the evolution of the stem form and assortments of wood in Pinus taeda L. stands. The planting was installed in the year of 2003, with 2.0 m x 2.0 m spacing; 3.0 m x 2.0 m and 4.0 m x 2.0 m and is located in the municipality of Irati, in the Center-South region of the State of Paraná, Brazil. A 100% forest inventory or census was carried out and, according to the diametric distribution, 136 trees were sampled to obtain dry biomass by tree components and also to evaluate the growth of dendrometric variables using the complete stem analysis technique (ANATRO). Each component of the tree was weighed, separately, and samples were collected and taken to the greenhouse at 70 ºC, to later quantify the dry biomass. Based on the biomass of each component, using an average carbon content of 0.45, carbon was also quantified. For the modeling of biomass, three models were tested: Hohenadl-Krenn, Schumacher-Hall and Husch. The discs, used in ANATRO, after being dried, were sanded and demarcated the growth rings that were measured with the LINTAB equipment and processed in FlorExel program. Based on ANATRO data, the average production of each dendrometric variable (diameter at 1.30 m above the ground, transversal area, total height, individual volume, basal area and volume per hectare) was determined. The Chapman-Richards model was used to describe the production curves for these variables, generating the curves of current annual increment (CAI) and average annual increment (MAI). ANATRO data were also used to analyze the evolution of the tree stem form using the artificial form factor and the adjustment of the 5th degree taper function for all sampled trees and by age class. These equations were used to estimate stem assortments and volume. The partitioning of biomass in the components of P. taeda trees, at 15 years old, presented the following accumulation sequence: stem, dead branches, live branches and needles. For the individual total biomass, ranged from 170.30 kg.ind-1 to 229.10 kg.ind-1 from the smallest spacing to the largest; and for the total biomass per hectare it was 223.78 Mg.ha-1 to 304.39 Mg.ha-1 , from the largest to the smallest spacing, respectively. Following the expected trend, for the individual dendrometric variables, the 4.0 m x 2.0 m spacing produced the largest dimensions, contrasting with the basal area and volume per hectare variables, where the highest values were in the 2.0 m x 2.0 m spacing. The artificial form factor at higher initial densities (2.0 m x 2.0 m) results in logs 7% more cylindrical than those found at lower densities. The 5th degree polynomial was suitable for all age groups, including non-grouped data (all ages). In the assortment at 10 years of age, 50% of the volume is destined for cellulose (8 to 17.99 cm in diameter at the thin end of the log), with greater volumes per hectare in the 2.0 m x 2.0 m spacing. The volume for type 2 sawmill (25 to 34.9 cm with 3.1 m in length) is greater in the 4.0 m x 2.0 m spacing from 9 years of age. Until the age evaluated (15 years) the analyzed spacing had not yet produced wood with a thin tip diameter greater than 35 cm and 3.1 m long, a class of assortment with greater added value.